A note on constructing sine and cosine functions in discrete fractional calculus - Ashley, Asa; Atıcı, Ferhan M.; Chang, Samuel (CUBO, A Mathematical Journal, 2025)
In this paper, we introduce two sets of linear fractional order \(h\)-difference equations and derive their solutions. These solutions, referred to as trigonometric functions of fractional \(h\)-discrete calculus, are proven to have properties similar to sine and cosine functions on \(R\). The illustrated graphs confirm these similarities.